MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Resma Hutapea; Nurhayati Nurhayati (Musamus University, 2019)
Abstract: This research aims to improve the results of learning math grade VIII B SMP Negeri 2 Merauke on material Composition functions and the inverse of a function through the application of cooperative learning, Jigsaw-type model. Design research is the research action class is done in two cycles with each cycle conducted two meetings. The subject of research as many as 27 students in grades VIII B SMP Negeri 2 Merauke. The instruments used in the form of tests and observation sheets. The results in this study is the increased Mastery Learning students at pre cycle of 33.3%, I cycle of 63% and cycle II by 89%. In addition the average value, the activity of teacher and student activity obtained also experienced an increase. Based on the results obtained in overall it can be concluded that the application of the cooperative learning model Jigsaw type can improve the results of learning math grade VIII B SMP Negeri 2 Merauke. Keywords: Cooperative Model Type Jigsaw, The Results Of The Learning Of Mathematics.